2010
DOI: 10.3340/jkns.2010.47.2.137
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Schwannoma Presenting with Acute Intracranial Subarachnoid Hemorrhage

Abstract: J Korean Neurosurg Soc 47 : [137][138][139] 2010 A subarachnoid hemorrhage (SAH) associated with negative finding on four-vessel angiography is seen in 5 to 30% of patients with intracranial SAH. A previously silent lesion in the spinal canal may be responsible for the angiographically negative finding for cause of intracranial SAH. We report a case of upper cervical (C1-2) intradural schwannoma presenting with acute intracranial SAH. Repeated cerebral angiographic studies were negative, but cervical magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Some masses caused occipital condyles erosion (18.7%), VA displacement (8.8%), brainstem compression (6.5%), 4th ventricle blockage (2.5%), and sigmoid sinus occlusion (1.1%). A total of 5 patients (1.4%) had concurrent CVJ intradural meningiomas separated from the extradural schwannomas [ 23 , 25 , 26 , 27 ], and 2 (0.6%) had acute subarachnoid hemorrhage (SAH) [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some masses caused occipital condyles erosion (18.7%), VA displacement (8.8%), brainstem compression (6.5%), 4th ventricle blockage (2.5%), and sigmoid sinus occlusion (1.1%). A total of 5 patients (1.4%) had concurrent CVJ intradural meningiomas separated from the extradural schwannomas [ 23 , 25 , 26 , 27 ], and 2 (0.6%) had acute subarachnoid hemorrhage (SAH) [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…9 However, our literature review revealed that seven patients (77%) exhibited intracranial clinical symptoms. 8 14 As arterial aneurysm and vascular malformation are the more common causes of SAH, an angiographic study may be the preferential examination to confirm the diagnosis. In our patient, spinal infection or SAH from vascular malformation was considered first.…”
Section: Discussionmentioning
confidence: 99%
“…6 Spinal intradural schwannomas may also result in SAH; however, these are a very rare cause, especially without spinal compression symptoms. In this summary, we identified 8 cases of SAH from a spinal schwannoma reported in the last 20 years [7][8][9][10][11][12][13][14] (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…A thorough search of literature led us to only 22 cases of spinal schwannomas with SAH till now. [ 6 29 30 ] In literature review that has the largest series on spinal schwannomas with SAH, Parmar et al . [ 6 ] identified 20 reports of spinal nerve sheath tumors that caused SAH, of which only 8 cases (28%) presented exclusively with intracranial symptoms as in our patient.…”
Section: Discussionmentioning
confidence: 99%